Serving the empire in the Great War the Cypriot Mule Corps, imperial loyalty and silenced memory - Varnava, Andrekos 1979- (Manchester University Press, 2017)
This book contributes to the growing literature on the role of the British non-settler empire in the Great War by exploring the service of the Cypriot Mule Corps on the Salonica Front, and after the war in Constantinople
Keywords: Great Britain / Army / History; European history / bicssc; Humanities / History / bicssc; HISTORY / General / bisach; First World War / c 1910 to c 1919 / thema; World War, 1914-1918 / Cyprus; World War, 1914-1918 / Campaigns / Macedonia; Mules / War use / Cyprus / History; Muleteers / Cyprus / History; Erster Weltkrieg; Cyprus / Foreign relations / Great Britain; Zypern